Local and imported wine at Pompeiopolis, Paphlagonia - Opaiţ, Andrei (Rei Cretariae Romanae Fautorum Acta, 2022)
The study of over 22000 diagnostic ceramic fragments provides a reliable basis for understanding social and economic life at Pompeiopolis. Based on amphora discoveries, the author discusses imported wine amphorae as a means for determining main supply centres as well as their periods of acme and disappearance. Results indicate that during the early- to mid-Roman periods the main suppliers were Aegean centres, followed by the Levantine products until the first decades of the 7th century, and by south and east Pontic wine amphorae during the middle and end of the 7th century. A revival of the settlement during the 10th–11th centuries is also attested by wine amphorae that arrived from the Sea of Marmara. However, this imported wine was minor in quantitative terms. Most wine must have been supplied by local producers, as is well attested by local amphorae and a large variety of jugs. The author concludes that when the desire of the local elite was sufficiently strong, they willingly paid the cost of expensive products and their transport costs.